EFFECT OF PARTICLE ROUNDNESS AND MORPHOLOGY ON THE SHEAR FAILURE MECHANISM OF GRANULAR SOIL UNDER STRIP FOOTING - Ghalehjough, Babak Karimi; Akbulut, Suat; Celik, Semet (UNIV MARIBOR, 2018)
This study investigates the effect of particles roundness and morphology on the shear failure mechanism of soil. A strip footing was modeled under laboratory conditions. Calcareous soil was tested with three roundness classes: angular, rounded and well-rounded shapes with sizes of 0.30 mm to 4.75 mm. These were divided into six different groups at three relative densities of 30%, 50% and 70%. A series of photographs was taken during the tests and analyzed using the particle image velocimetry (PIV) method to understand the soil-deformation mechanism. The results showed that increasing the sample sizes increased the affected area of the soil. At the same time, increasing the relative density caused a punching failure mechanism that went towards the general failure. The shear failure mechanism of the soil changed from general toward punching shear failure with increasing particle roundness. This effect was larger with the smaller materials. Underneath the affected layers of soil, the angular samples were deeper than the rounded and well-rounded samples. The affected depth in the angular soil was approximately 1.5B in the smallest size group. This was more than 3B and near 4B in the largest size group. Both the sides and the underlying soil layers should be considered on angular soils. The area under the footing becomes more important than the side parts after increasing the roundness of the particles.
Keywords: particler roundness; morphology of particles; shear failure mechanism; strip footing; PIV method; ultimate bearing capacity; IMAGE VELOCIMETRY PIV; DEFORMATION MEASUREMENT; SAND; SETTLEMENT; SHAPE; Engineering